Effects of a shoot training programme with a reduced hoop diameter rim on free-throw performance and kinematics in young basketball players - Khlifa, R.; Aouadi, R.; Shephard, R.; Chelly, M. S.; Hermassi, S.; Gabbett, T. (Journal of Sports Sciences, 2013)
The present paper investigated the effects of a shoot training programme with a reduced hoop diameter (0.35 m) rim on kinematics and performance of basketball free-throws. Eighteen young male basketball players were divided into control (CG, n = 9) and experimental (EG, n = 9) groups. Both groups undertook a 10-week training programme comprising two training sessions per week. Under fatigued conditions, each participant shot 150 free-throws in each training session, with the CG using a standard rim, and the EG a smaller rim. All other training was identical between groups. Ball release parameters, player's kinematics and mean of successful free-throws (out of 150 attempts) were determined for each participant, before and after completion of the training programme. Following training, a significant increase (P < 0.05) in ball release angle, speed and height and in shoulder joint angle at release (P < 0.01) was observed for the EG. Both the CG (P < 0.001) and the EG (P < 0.0001) showed an increase in the number of successful free throws, although the increase was greater (P < 0.05) for the EG (22.7 ± 6.4 free throws) than for the CG (14.6 ± 7.8 free throws). We conclude that training with a reduced rim significantly improves free-throw performance in young basketball players.